2022
DOI: 10.1155/2022/2731007
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Network Analysis of Patients with Primary Angle-Closure Glaucoma

Abstract: Objectives. Recent resting-state functional magnetic resonance imaging (fMRI) studies have focused on glaucoma-related neuronal degeneration in structural and spontaneous functional brain activity. However, there are limited studies regarding the differences in the topological organization of the functional brain network in patients with glaucoma. In this study, we aimed to assess both potential alterations and the network efficiency in the functional brain networks of patients with primary angle-closure glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The ORBsupmed-L (left superior frontal gyrus orbital region) and ORBsupmed-R (right superior frontal gyrus orbital region) are located in the prefrontal region. A study revealed the central disappearance of the left superior frontal gyrus orbital part in POAG (42), whereas another study demonstrated enhanced local indicators in this area among PACG patients (43).…”
Section: Discussionmentioning
confidence: 97%
“…The ORBsupmed-L (left superior frontal gyrus orbital region) and ORBsupmed-R (right superior frontal gyrus orbital region) are located in the prefrontal region. A study revealed the central disappearance of the left superior frontal gyrus orbital part in POAG (42), whereas another study demonstrated enhanced local indicators in this area among PACG patients (43).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, this study found decreased GMV in ACC, parietal gyrus, and middle temporal gyrus in DON groups. The middle temporal gyrus is a part of the dorsal visual pathway, which may be associated with visual memory, 32 indicating the dorsal visual pathway may also be involved after the loss of inhibition inputs of the primary visual cortex 33 . Furthermore, these abnormal brain regions are responsible for emotional processes, thinking processes, and higher cognitive activities 16,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The middle temporal gyrus is a part of the dorsal visual pathway, which may be associated with visual memory, 32 indicating the dorsal visual pathway may also be involved after the loss of inhibition inputs of the primary visual cortex. 33 Furthermore, these abnormal brain regions are responsible for emotional processes, thinking processes, and higher cognitive activities. 16,34 A recent large sample cross-sectional study conducted in the United States has demonstrated that vision impairment is associated with a substantial proportion of dementia cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al 12 found that the degree centrality (DC) values of bilateral visual cortex and left anterior central gyrus in PACG patients after surgery were signi cantly higher than those before surgery. Liu et al 13 determined that the brain networks of PACG patients had small-world properties, indicating that the brain networks of PACG patients had abnormal information transmission e ciency. The above studies suggest that patients with PACG exhibit speci c functional irregularities within interregional and global brain networks.…”
Section: Introductionmentioning
confidence: 99%